Analisis Kesulitan Siswa Dalam Operasi Pembagian Serta Dampaknya Terhadap Hasil Belajar Matematika Di Kelas VI SDN 19 Ampenan - Gina Salsabila; Nafisa Maula Amelia; Berliana Isratunnisah; Septiana Septiana; Nurul Fitrih; Djuita Hidayati (Science and Education Journal (SICEDU), 2026)
This study aims to analyze students’ difficulties in division operations and their impact on the mathematics learning outcomes of sixth-grade students at SDN 19 Ampenan. This research employed a qualitative approach, with data collected through observation, interviews, and documentation. The findings indicate that students experience various difficulties in understanding the concept of division, both as the inverse of multiplication and as repeated subtraction. In addition, students face challenges in determining quotients, following the procedures of long division, and solving word problems. These difficulties are influenced by students’ weak mastery of basic arithmetic operations, particularly multiplication and subtraction. The impact of these difficulties is reflected in the low mathematics learning outcomes, as indicated by the large number of students who have not achieved the Minimum Mastery Criteria. The average student score is 48, which is still below the established minimum standard of 75.